A Simulation of International Climate Regime Formation. (April 2013) - Kauneckis, Derek L.; Auer, Matthew R.
The literature on pedagogical methods in international affairs includes a number of international politics simulations. We present the material for an in-class simulation exercise on international climate negotiations that attempts to help students understand the importance of theory as well as the substantive issues surrounding climate policy. Simulations have been proposed as a means of providing an engaging classroom experience and a more diverse learning experience. The exercises presented here focus on developing student research skills, analyzing data to present a realistic policy position and understanding the process of institutional regime formation. At the end of the simulation, students are asked to relate their own negotiation experiences back to the theoretical material discussed during the semester. An assessment was conducted of student expectations prior to the simulation exercise and compared with post-simulation experiences. Students reported the greatest positive difference between their expected learning outcome and actual experience with the simulation in terms of learning information about specific country assignments, overall enjoyment of the activity, and understanding the material covered in the course. The greatest negative difference between expectations and experience were reported for understanding international negotiations more generally and current international events. The article outlines the full content for an in-class simulation and its' implementation as well as results from an evaluation of its use. The simulation provides students with a better understanding of the complexity of international negotiations over climate policy while outlining key theoretical concepts in international relations and comparative public policy.